Study of using dolomite ores as raw materials to produce magnesium phosphate cement. (30th August 2020) - Yu, Jincheng; Qian, Jueshi; Wang, Fan; Qin, Jihui; Dai, Xiaobing; You, Chao; Jia, Xingwen
Highlights: MPC cements have been successfully prepared by using dolomite as raw material. The calcination model of fine dolomite particles and coarse quartz particles was proposed. MPC pastes with sample T1200-R1.5 showed the highest 3 h-compressive strength of 37 MPa. Abstract: Although magnesium phosphate cement (MPC) is a type of chemically bonded ceramic with many vital properties, the practical application is limited by the high cost of raw materials. Dead burned MgO generally obtained from calcination of magnesite is used in MPC production. Dolomite as another abundant magnesium resource is widely distributed and has larger deposits than magnesite. This paper aims to replace magnesite with dolomite as raw materials to reduce the cost in MPC production. Quartz powders were also introduced in the calcination process to chemically combine with CaO components in dolomite. The effect of calcination temperature and dolomite-to-quartz mass ratio on the properties of calcined raw material were investigated. After calcination, the influence of dolomite-quartz powders under different calcination conditions on the performance of MPC pastes was assessed by observing the setting time, compressive strength, phase development and microstructure of hydration products as well as soundness. The calcination model of fine dolomite particles and coarse quartz particles was proposed to guarantee less free-CaO and more MgO after calcination. When the setting time of MPC prepared by the sample T1250-R1.5 was 16 min, the compressive strength of the pastes could reach 22 MPa at curing age of 3 h and 63 MPa at 7 d, with sufficient soundness and safety by preliminary judgment. The relatively lower calcination temperature at 1250 °C compared to conventionally prepared dead burnt magnesite would significantly reduce energy consumption and operating costs in production of magnesium bearing raw material for MPC.